PENGARUH RELIGIUSITAS DAN PENGETAHUAN PRODUK HALAL TERHADAP PENILAIAN PRODUK HALAL DAN MINAT PEMBELIAN PRODUK HALAL (Studi Kasus Pada Industri Makanan - Visca Mirza Vristiyana (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2019)
In this modern era, many product companies are competing to produce food products thatcontain halal-labeled ingredients for food products made by the wider community.The populationin this study were Islamic students in the city of Semarang who had issued halal products. Thesample in this study are some Islamic students who have spent halal food products. Techniquesin sampling in this study, using purposive sampling techniques or sampling. The purposivesampling technique is a sampling technique that adjusts to certain criteria (intentional). Analysistools that are multiple linear regression.The results showed that Instrinsik Religiosity positivelyand significantly toward the assessment of halal products, extrinsic religiosity positively andsignificantly towards the assessment of halal products, halal product knowledge had a positiveand significant effect on halal products, instrinsic significant religiosity to buy halal products,extrinsic religiosity significantly and significantly on the purchase price of halal goods, halal hasa positive and significant influence on the purchase price and an assessment of halal productshas a positive and significant effect on the purchase price of halal productsKeywords: religiosity and knowledge of halal products, halal products and interest inpurchasing products